Government Ownership and Managers’ Role: Effect to Acquisition Return Among High-Technology Companies - Norhamiza Ishak; Hanita Kadir Shahar; Kamarun Nisham Taufil Mohd (Asian Academy of Management Journal of Accounting and Finance, 2023)
This study investigates the effect of high-technology (high-tech) company acquisitions and GLIC ownership on shareholders’ value creation. Study samples for empirical analyses were carried out using the market-model event-study and multivariate analysis on studies published between 2011 and 2018. The findings indicate that; (i) The CAR for high-tech acquiring firms for the three-day event window (–1,1), five-day event window (–2, +2) and 11-day event window led to significant positive returns, with at least at 10% level, signifying that investors have a favourable reaction towards short-term high-tech acquisitions; (ii) The relationship between the GLICs’ Institutional Blockholders (BPSVGLIC) and executive director (FRACEXEC) was found to affect the abnormal returns significantly negatively at a minimum 5% significance level. These results provide two practical implications; firstly, investors gain abnormal returns from their investment in high-tech acquiring companies, and secondly, firms with greater ownership stakes in GLICs could experience value destruction.